Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/su10124852
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Timely Adjustment of the Grazing Prohibition Policy: Ban or Lift? Empirical Research from Local Government Managers

Abstract: As national policy implementers and regional development planners, local government managers have a clearer, more objective and comprehensive understanding of ecological changes than herdsmen. Thus, they have a significant impact on the sustainable development of grassland resources and agricultural and pastoral areas. In this paper, grassland ecological change and related factors in different stages were investigated by means of questionnaires and structured interviews, and the adjustment strategies of grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The higher the satisfaction of the herders with the grassland ecological compensation mechanism, the more willing they will be to carry out feeding and breeding in accordance with the policy requirements, which will be more beneficial to grassland ecological restoration. This approach is consistent with the research results the study of Zhou et al Zhou et al found that raising the standard of ecological compensation will encourage farmers to reduce grazing [41]. Hu et al pointed out that when herders are provided with sufficiently high ecological compensation, they are more willing to change the method of grassland use [17].…”
Section: The Satisfaction Of Herders With the Grassland Ecological Compensation Mechanisms Is Helpful To Alleviate Their Grazing Behaviorsupporting
confidence: 80%
See 1 more Smart Citation
“…The higher the satisfaction of the herders with the grassland ecological compensation mechanism, the more willing they will be to carry out feeding and breeding in accordance with the policy requirements, which will be more beneficial to grassland ecological restoration. This approach is consistent with the research results the study of Zhou et al Zhou et al found that raising the standard of ecological compensation will encourage farmers to reduce grazing [41]. Hu et al pointed out that when herders are provided with sufficiently high ecological compensation, they are more willing to change the method of grassland use [17].…”
Section: The Satisfaction Of Herders With the Grassland Ecological Compensation Mechanisms Is Helpful To Alleviate Their Grazing Behaviorsupporting
confidence: 80%
“…This study found that the number of young and middle-aged laborers has a significant mediating effect on grassland dependence and grazing behavior. An increase in livelihood diversity will prompt herders to reduce grazing behavior, consistent with the research of Zhou et al [41]. They believe that promoting the livelihood diversification and non-agriculturalization of farmers can effectively promote farmers' reduction of livestock.…”
Section: Family Characteristics Has a Positive Effect On Reducing Grazing Behaviorsupporting
confidence: 79%
“…In order to mitigate the effects of grassland degradation on the Tibetan Plateau, China has invested~7 billion USD. One example program is "Returning Grazing Land to Grassland", which facilitates grazing exclusion by building fences, has been implemented since 2003 [42]. Understanding the effects of restoration practices on the ecosystem are important for sustainable development [43,44].…”
Section: Implications For Sustainable Grassland Management Strategiesmentioning
confidence: 99%
“…Direct evidence is needed for determining what time is ''safe'' to start grazing, given that the local policy of seasonal grazing is purely relied on the empirical mode [51]. For example, Wulagai grassland in the east of Inner Mongolia has an open season for grazing since May 20th (DOY 140).…”
Section: Application To Inner Mongolia Grasslandmentioning
confidence: 99%